Endometrial disease diagnosed by transvaginal ultrasound and dilatation and curettage - (:unkn) unknown (MUNKSGAARD INT PUBL LTD, 1999)
Background This study is designed to compare endometrial thickness measured by transvaginal ultrasound with endometrial pathology by dilatation and curettage. Methods. Fifty-four women with postmenopausal bleeding were evaluated. Endometrial thickness, including both layers of the endometrium, was measured by transvaginal ultrasound after which fractional curettage was performed and samples taken were then dispatched for histologic examination. Results. Median endometrial thicknesses of 5 mm, 8.5 mm and 6 mm were found for benign, hyperplastic and carcinomatous endometrium, respectively. Of the eight hyperplastic samples, two cases had 4 mm, and one case had 3 mm endometrial thickness. Similarly of the nine malignant samples, three cases had an endometrial thickness of 3 mm. Three Mn has been found to be the best cut off point for endometrial abnormalities in postmenopausal bleeding with 100% sensitivity but low specificity (13%). Conclusion. Fractional curettage seems to be the best method for detecting endometrial abnormalities in women with postmenopausal bleeding.
Keywords: cancer; endometrial thickness; postmenopausal bleeding; ABNORMAL ENDOMETRIUM; POSTMENOPAUSAL WOMEN; THICKNESS; PERIMENOPAUSAL; SONOGRAPHY